Sustainable Agropreneurship Strategies through the Optimization of Palm Oil-Based Chocolate Bar Formulations - Abdul Rizal (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
The development of sustainable agropreneurship is a crucial strategy to enhance the added value of agricultural and plantation commodities, particularly in the cocoa and palm oil industries. One promising innovation is the formulation of palm oil-based chocolate bars, serving as an alternative or complement to cocoa butter. This literature review aims to analyze optimization strategies for chocolate bar formulations utilizing palm oil to support the sustainability of agropreneurial ventures. The research method employed is a comprehensive review of recent scholarly sources (2018–2024) addressing processing technology, physicochemical properties, consumer acceptance, as well as economic and environmental impacts. The findings indicate that the incorporation of palm oil in chocolate bar formulations has the potential to reduce production costs, improve product stability, and create new market opportunities. Moreover, integrating palm oil utilization with sustainability principles can reduce dependence on imported cocoa butter and increase the added value of domestic palm oil. Challenges include adjusting the formulation composition to preserve the distinctive chocolate flavor, complying with international quality standards, and addressing consumer perceptions regarding palm oil. This study recommends collaboration among farmers, industry stakeholders, researchers, and government bodies to promote innovation in products derived from local commodities. Therefore, optimizing palm oil-based chocolate bar formulations can serve as a sustainable agropreneurship strategy that synergizes economic, social, and environmental dimensions.